2013
DOI: 10.1007/s10661-013-3364-3
|View full text |Cite
|
Sign up to set email alerts
|

Leaching behaviour of chlorpyriphos and cypermethrin in sandy loam soil

Abstract: The mobility of chlorpyriphos and cypermethrin in sandy loam soil was studied in soil columns under laboratory conditions at two application rates, 25 and 50 μg, with simulated rainfall of 300 mm. Residues of chlorpyriphos and cypermethrin in soil and leachate were estimated by gas-liquid chromatography and confirmed by gas chromatography-mass spectrometry. Though maximum concentration of both the insecticides was found in the top 10-cm layer, chlorpyriphos was found distributed in the soil up to a depth of 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The reduced retention in the deeper horizons indicates a relation to organic carbon that also diminishes at higher depths, varying from 1.5% (Ap) to 0.47% (Bw1). These K oc values are relatively high, indicating that chlorpyrifos presents a low mobility in soil and a correspondingly low potential for groundwater contamination as reported by Rani et al and Laabs et al…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The reduced retention in the deeper horizons indicates a relation to organic carbon that also diminishes at higher depths, varying from 1.5% (Ap) to 0.47% (Bw1). These K oc values are relatively high, indicating that chlorpyrifos presents a low mobility in soil and a correspondingly low potential for groundwater contamination as reported by Rani et al and Laabs et al…”
Section: Resultsmentioning
confidence: 58%
“…The reduced retention in the deeper horizons indicates a relation to organic carbon that also diminishes at higher depths, varying from 1.5% (Ap) to 0.47% (Bw1). These K oc values are relatively high, indicating that chlorpyrifos presents a low mobility in soil and a correspondingly low potential for groundwater contamination as reported by Rani et al 29 and Laabs et al 25 For α-endosulfan K D values were 50 mL g −1 in Bw1, 324 mL g −1 in BA, and 288 mL g −1 in Ap horizons (corresponding to K oc from 8725 to 31992 mL g −1 ). β-Endosulfan showed a similar behavior to the α isomer with higher retention in the BA horizon (K d equal to 46.7 mL g −1 in Bw1, 405 mL g −1 in Ap, and 451 mL g −1 in BA with K oc varying from 8186 to 53080).…”
Section: ■ Materials and Methodsmentioning
confidence: 55%
“…For example, chlorpyrifos is degraded within approximately 10 days in a 0-15 cm and 40-60 cm clayey sandy soil. However, Rani et al [82] found that pesticides exist in the top 10 cm of soil. For example, chlorpyriphos and cypermethrin were found distributed to a depth of 35 and 15 cm of soil, respectively.…”
Section: Pesticide Residuesmentioning
confidence: 99%
“…10 The behavior, dissipation, and environmental fate of cypermethrin in the environment has been studied extensively as reported by researchers throughout the world. [13][14][15][16][17][18][19] Limited information could be found on the fate of other pesticides in the oil palm agroenvironment including a study on the persistence of diuron in the soil of an oil palm plantation in Malaysia, 20 leaching and persistence of benomyl in an oil palm nursery, 21 a study on the fate of thiram in an oil palm nursery during the wet season 22 and a study on the movement of chlorpyrifos in the soil of an oil palm plantation in Malaysia. 23 However, there has been no study undertaken on the behavior of cypermethrin in an oil palm agroenvironment.…”
Section: Introductionmentioning
confidence: 99%